TURNOVER INTENTION: A LITERATURE REVIEW - Cahya Purnama Asri (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
The objective of this research is to determine the variables associated with turnover intention. I presented a literature study and as a result of this process, 23 articles are included and then examined the bibliographical references to check the validity of the inquiry. I identify several variables that affect turnover intention and affected by it. Keywords: turnover intention; literature review